The Relationship Between Low and High Sodium and Potassium Levels and Blood Pressure in Both Genders of Different Ages - Amani ALayat; Ebtisam Bazzaqah; Retage Jumaa; Takwa Edal; Amjad Break; Uomna Al-Dawe (AlQalam Journal of Medical and Applied Sciences, 2026)
Hypertension is a major global health concern influenced by multiple factors, including electrolyte imbalances. Sodium and potassium play critical roles in blood pressure regulation, yet their effects may vary based on gender and age. This study investigates the relationship between sodium and potassium levels and blood pressure among males and females of different age groups to provide insights into hypertension risk factors and management strategies. A total of 90 participants were recruited and categorized into control and patient groups. The sample consisted of 50 males and 40 females, with 40 participants in the control group and 50 in the patient group. Blood samples were analyzed to determine sodium and potassium concentrations, and blood pressure measurements were recorded. The mean and standard deviation of these parameters were compared across gender and age groups. Pearson correlation analysis was performed to assess relationships between sodium, potassium, and blood pressure in male and female participants. The study found that sodium levels were generally higher in male participants compared to females, with a stronger correlation between sodium and blood pressure observed in female patients. Potassium levels showed a negative correlation with blood pressure, particularly in males, suggesting a protective effect. Additionally, older participants exhibited greater sensitivity to electrolyte imbalances, indicating that age plays a crucial role in blood pressure regulation. Statistical analysis revealed significant gender-based differences in how sodium and potassium levels influence blood pressure, supporting the need for personalized dietary and medical recommendations. The findings suggest that high sodium intake contributes to elevated blood pressure, especially in female patients, while increased potassium levels may help lower blood pressure, particularly in males. Age-related variations highlight the importance of monitoring electrolyte balance in older individuals. These results reinforce the importance of dietary modifications that reduce sodium and enhance potassium intake as part of hypertension management strategies. Future research should explore gender-specific and age-related interventions to optimize cardiovascular health.